Exposure of okadaic acid alters the angiogenesis in developing chick embryos. (July 2017) - Jiao, Yu-hu; Dou, Min; Wang, Guang; Li, Hong-ye; Liu, Jie-sheng; Yang, Xuesong; Yang, Wei-dong
Abstract: Okadaic acid (OA) is a common phycotoxin, which concerns diarrheic shellfish poisoning (DSP) in human being. It has been known that OA can induce disorganization in cytoskeletal architecture and cell-cell contact, cause chromosome loss, apoptosis, DNA damage and inhibit phosphatases, suggesting its potential embryotoxicity. In this paper, we found that low concentration of OA (50 nM, 100 nM and 200 nM) significantly reduced the density of vascular plexus in yolk-sac membrane (YSM) of chick embryo, while high concentration of OA (500 nM) distinctly depressed the blood vessel density in chorioallantoic membrane (CAM). After exposed to OA, MDA level and SOD activity increased significantly in CAM tissues. However, addition of vitamin C could rescue OA-suppressed angiogenesis in CAM of chick embryo. After exposure of OA, Ang-2 expression was down-regulated in CAM tissues. Taking together, we proposed that OA interfered with angiogenesis in developing chick embryo, through, at least partly, the induction of excessive ROS generation. Highlights: OA could interfere with angiogenesis in developing chick embryo. Vitamin C could rescue the OA-inhibited angiogenesis in CAM. Negative impact of OA on angiogenesis might be related to oxidative stress. Our results might provide more information on the embryotoxicity of OA.